2019
DOI: 10.1177/1533033819841061
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison Between Jaw Tracking and No Jaw Tracking in Intensity-Modulated Radiation Therapy

Abstract: Purpose: This article compares the dosimetric differences between jaw tracking and no jaw tracking technique in static intensity-modulated radiation therapy plans of large and small tumors. Methods: Eight plans with large tumor (nasopharyngeal carcinoma, volume range: 510.9 to 768.0 cm3) and 8 plans with small tumor (single brain metastasis, volume range: 5.3 to 9.9 cm3) treated with jaw tracking on Varian EDGE LINAC were chosen and recalculated with no jaw tracking to study the dosimetric differences. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The extent of the reduction may be related to the location and volume of the target being irradiated. In addition, our results confirmed that the JA‐IMRT/ JT‐VMAT groups could slightly increase treatment plan MUs which were consistent with the previous study 29 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The extent of the reduction may be related to the location and volume of the target being irradiated. In addition, our results confirmed that the JA‐IMRT/ JT‐VMAT groups could slightly increase treatment plan MUs which were consistent with the previous study 29 …”
Section: Discussionsupporting
confidence: 92%
“…In addition, our results confirmed that the JA-IMRT/ JT-VMAT groups could slightly increase treatment plan MUs which were consistent with the previous study. 29 There are several limitations in the present study that we should pay attention to. First, the number of patients for the current research were small, since only 10 cases from each category of lung cancer were involved, and all of the baseline characteristics might have a possible adverse influence.…”
Section: F I G U R Ementioning
confidence: 86%
See 1 more Smart Citation
“…This arrangement decreases the undesired doses delivered to normal tissue and organs at risk (OARs), compared to the arrangements in the static jaw technique (SJT). [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Several authors have explored the patient protection potential improvements in intensitymodulated radiotherapy (IMRT) with JTT. Schmidthalter et al analysed this issue in three academic and two clinical IMRT cases.…”
Section: Introductionmentioning
confidence: 99%
“…They noticed that the benefits of JTT plans were greater for NPC patients with larger tumour volumes and treatment fields. 12 Raj Mani et al estimated the influence of JTT in head and neck cancer patients compared to the static technique. The dose reductions with JTT in V5, V10, V20, V30 and Dmean ranged from 2 to 5% in IMRT plans and from 1 to 3% in VMAT plans.…”
Section: Introductionmentioning
confidence: 99%